Copper chromium oxide spinel, resin composition thereof, and resin molded article

The particle size distribution and calcining process optimization of copper oxide chromium spinel are controlled by laser diffraction-scattering method, and the problem of uneven dispersion of copper oxide chromium spinel in the resin is solved, and the excellent adhesiveness of plating and molded products are achieved. Surface smoothness.

CN119173481APending Publication Date: 2024-12-20DIC CORP
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202380038749.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-06-02
Filing Date
2023-05-25
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

The existing copper oxide chromium spinel and its manufacturing methods fail to effectively control the particle size distribution, resulting in uneven dispersion in the resin, affecting the adhesion and surface roughness of the plating.

Method used

The particle size distribution of copper oxide chromium spinel is controlled by laser diffraction-scattering method to ensure uniform dispersion in the resin. The copper oxide chromium spinel is manufactured by specific calcining and mixing processes, optimize its particle size and shape, and increase molybdenum or the presence of sodium to improve catalytic activity.

Benefits of technology

The excellent adhesion of copper oxide chromium spinel in the resin and plating is achieved, and the surface smoothness and plating performance of the molded product are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119173481A_ABST
    Figure CN119173481A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide: a copper-chromium oxide spinel having excellent dispersibility in a resin composition and excellent adhesion to plating; a resin composition containing the copper-chromium oxide spinel; and a resin molded article. Specifically, provided is a copper-chromium oxide spinel in which, in the particle size distribution obtained by a laser diffraction scattering method in terms of volume, when the particle sizes with cumulative frequencies of 10%, 50%, and 90% from the small particle size side are D10, D50, and D90, respectively, the extension of the particle size distribution SPAN = (D90-D10) / D50 is 2 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a copper chromium oxide spinel having a controlled particle size distribution, and a resin composition and a molded product containing the copper chromium oxide spinel. Background Art

[0002] In recent years, the fields of electronics and mechatronics have been promoting the miniaturization, lightweighting, and multifunctionalization of equipment. In particular, in the automotive field, connectivity, service, and automation are being promoted, and sensors or modules are increasing. On the other hand, the weight of the vehicle is required to be suppressed towards electrification, and there is a strong demand for lightweight and miniaturization of mechanical parts and electrical circuit parts. As a technology that can cope with this, technologies related to molded circuit parts (molded interconnect devices (MID)) have attracted attention. The so-called MID is a technology for molding circuits, electrodes, etc. on resin molded products. By integrating circuits, electrodes, etc. with resin molded products, it is possible to achieve miniaturization and lightweighting of parts.

[0003] MID includes: a one-shot molding method in which the surface of a resin molded product is roughened and then plated; a two-shot molding method in which a circuit-forming resin and an insulating portion-forming resin are molded twice and integrated; and a hot stamping method in which a circuit is directly formed in a resin molded product using a die.

[0004] Among these, laser direct structuring (LDS) technology, which is a one-step forming method, has attracted particular attention from the perspectives of reducing manufacturing costs and being able to produce ultra-fine circuits in a short period of time. In addition, the so-called LDS technology is a technology that can form a strong plating layer on the laser irradiated part by roughening the surface of the laser irradiated part and activating the additive when a resin molded product containing a specified additive is irradiated with laser.

[0005] Therefore, research on additives applicable to LDS technology is being promoted. As additives, spinel metal oxides are generally used (Patent Document 1, Patent Document 2). In particular, from the perspective of adhesion to copper-plated patterns, spinel metal oxides containing copper can be flexibly utilized.

[0006] Patent Document 1 discloses a conductor track structure comprising: a high oxide having a spinel structure having high thermal stability and durability in an acidic or alkaline aqueous metallizing electrolyte, or a simple d-metal oxide or a mixture thereof, or a mixed metal oxide similar to a spinel structure.

[0007] Patent document 2 shows a thermosetting resin composition for LDS, which includes a non-conductive metal compound, which includes one or more selected from the group consisting of spinel metal oxides, metal oxides having two or more transition metal elements selected from Groups 3 to 12 of the periodic table and adjacent to the groups, and tin-containing oxides, and forms a metal core by irradiation with active energy lines.

[0008] Patent Document 3 discloses a thermoplastic composition having improved plating performance, and shows that the composition contains a metal compound represented by AB2O4 in an amount of 1 wt% relative to the weight of the raw composition.

[0009] However, the patent documents use commercially available metal oxides and the like, and do not conduct sufficient research on metal oxides. For example, if the particle size distribution is not controlled, the metal oxide will not be uniformly dispersed in the resin, or the surface will become rough due to the presence of coarse particles on the surface of the hardened material, resulting in problems such as uneven adhesion of the plating or uneven plating treatment. Therefore, copper chromium oxide spinel with a specified particle size distribution or particle diameter is required, but the existing knowledge of copper chromium oxide spinel and its manufacturing method is limited, and there is still room for research.

[0010] Prior art literature

[0011] Patent Literature

[0012] Patent Document 1: Japanese Patent Publication No. 2004-534408

[0013] Patent Document 2: International Publication No. 2017 / 199639

[0014] Patent Document 3: Japanese Patent Publication No. 2015-501868 Summary of the invention

[0015] Problems to be solved by the invention

[0016] Therefore, the present invention has been made to solve the above-mentioned problems, and an object of the present invention is to provide a copper chromium oxide spinel having a controlled particle size distribution, and a resin composition containing the copper chromium oxide spinel.

[0017] Technical means of solving problems

[0018] The present inventors have conducted intensive research to solve the above-mentioned problems and have found that by controlling the particle size distribution of copper chromium oxide spinel, the surface of the cured product of the obtained resin composition becomes smooth, the plating is formed uniformly, and the adhesion is excellent, thereby completing the present invention.

[0019] That is, the present invention has the following aspects.

[0020] (1) A copper chromium oxide spinel, wherein in a volume-converted particle size distribution obtained by a laser diffraction scattering method, when the particle sizes with cumulative frequencies of 10%, 50%, and 90% from the small particle size side are set as D10, D50, and D90, respectively, an expansion span (SPAN) of the particle size distribution = (D90-D10) / D50 is less than 2.

[0021] (2) The copper chromium oxide spinel according to (1), wherein D50 is 5.0 μm or less.

[0022] (3) The copper chromium oxide spinel according to (1) or (2), wherein D90 is 10.0 μm or less.

[0023] (4) The copper chromium oxide spinel according to any one of (1) to (3), wherein the copper chromium oxide spinel has an octahedral shape.

[0024] (5) The copper chromium oxide spinel according to (1) above, further comprising molybdenum.

[0025] (6) A resin composition comprising: the copper chromium oxide spinel according to any one of (1) to (5);

[0026] Thermoplastic resin or thermosetting resin; and

[0027] Inorganic filler.

[0028] (7) A resin molded article obtained by molding the resin composition according to (6).

[0029] Effects of the Invention

[0030] The present invention can provide copper chromium oxide spinel with controlled particle size distribution.

[0031] Furthermore, according to the present invention, a resin composition containing the copper oxide chromium spinel having excellent plating adhesion, and a molded product thereof can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] [ Figure 1 ] is the SEM image of the copper chromium oxide spinel of Example 1.

[0033] [ Figure 2 ] is the SEM image of the copper chromium oxide spinel of Example 2.

[0034] [ Figure 3 ] is the SEM image of the copper chromium oxide spinel of Example 3.

[0035] [ Figure 4] is the SEM image of the copper chromium oxide spinel of Example 4.

[0036] [ Figure 5 ] is the SEM image of the copper chromium oxide spinel of Example 5.

[0037] [ Figure 6 ] is the SEM image of the copper chromium oxide spinel of Example 6.

[0038] [ Figure 7 ] is a SEM image of the copper chromium oxide spinel of Comparative Example 1.

[0039] [ Figure 8 ] is a SEM image of the copper chromium oxide spinel of Comparative Example 2.

[0040] [ Fig. 9 ] is an evaluation image for metal element analysis.

[0041] [ Fig.10 ] is the spectral line profile of Cr in the EDS line analysis of Example 1.

[0042] [ Fig.11 ] is the spectral line profile of Cu in the EDS line analysis of Example 1.

[0043] [ Fig.12 ] is the spectral line profile of Cr in the EDS line analysis of Example 3.

[0044] [ Fig.13 ] is the spectral line profile of Cu in the EDS line analysis of Example 3.

[0045] [ Fig.14 ] is the spectral line profile of Cr in the EDS line analysis of Example 4.

[0046] [ Fig.15 ] is the spectral line profile of Cu in the EDS line analysis of Example 4.

[0047] [ Fig.16 ] is the spectral line profile of Cr in the EDS line analysis of Comparative Example 1.

[0048] [ Fig.17 ] is the spectral line profile of Cu in the EDS line analysis of Comparative Example 1. DETAILED DESCRIPTION

[0049] Hereinafter, embodiments of the copper chromium oxide spinel, a method for producing the copper chromium oxide spinel, and a resin composition containing the particles of the present invention will be described.

[0050] <Copper chromium oxide spinel>

[0051] The spread of the particle size distribution of the copper chromium oxide spinel of the embodiment calculated by the laser diffraction-scattering method may be less than 2, less than 1.9, or less than 1.5. By being within the above range, the dispersibility in the resin is excellent, and the adsorption characteristics of the plating when the molded product is made are excellent, which is preferred.

[0052] In this specification, the spread of the particle size distribution calculated by the laser diffraction-scattering method is calculated using the following conversion formula.

[0053] Spread of particle size distribution: SPAN = (D90-D10) / D50

[0054] In addition, each particle diameter of D10, D50, and D90 refers to a particle diameter at which the cumulative frequency from the small particle diameter side is 10%, 50%, and 90% in the volume-converted particle size distribution obtained by a laser diffraction scattering method.

[0055] The median diameter D50 of the copper chromium oxide spinel of the embodiment calculated by laser diffraction-scattering method is preferably 5.0 μm or less, more preferably 0.5 μm to 4.0 μm, and particularly preferably 1.0 μm to 3.0 μm. The median diameter D50 is preferably within the above range because the plating adsorption performance is improved when the LDS resin composition is prepared.

[0056] The median particle size D90 of the copper chromium oxide spinel of the embodiment calculated by the laser diffraction-scattering method is preferably 10 μm or less, more preferably 1.0 μm to 9.0 μm, more preferably 2.0 μm to 8.0 μm, and particularly preferably 2.5 μm to 4.0 μm. By being within the above range, when the LDS resin composition is prepared, the coarse particles can be used to reduce the unevenness of the molded surface, thereby improving the plating adsorption performance, which is preferred.

[0057] In this specification, the particle shape is controlled, which means that the particle shape is not amorphous. That is, the copper chromium oxide spinel with controlled particle shape in this specification means the copper chromium oxide spinel with non-amorphous particle shape.

[0058] The copper chromium oxide spinel of the embodiment may also have a polygonal shape. In particular, it is preferably a rectangular parallelepiped, a cube, a polyhedron, a triangular hammer, and a quadrangular hammer, more preferably a rectangular parallelepiped, a cube, and a polyhedron, and further preferably a polyhedron, and particularly preferably an octahedron. By having the above shape, it is preferred to have a high crystallinity with a single crystal structure. The crystal shape of the copper chromium oxide spinel of the embodiment is controlled, and it may have a polygonal shape. The copper chromium oxide spinel with a controlled crystal shape can be manufactured, for example, by the method for manufacturing the copper chromium oxide spinel of the embodiment described later.

[0059] In the case of copper chromium oxide spinel having an octahedral shape, preferably 50% or more of the particles have an octahedral shape based on mass or number, more preferably 80% or more of the particles have an octahedral shape, and even more preferably 90% or more of the particles have an octahedral shape.

[0060] Whether it is high crystallinity can be determined by using SmartLab (manufactured by Rigaku Co., Ltd.) as an X-ray diffraction device, using a high-intensity / high-resolution crystal analyzer (CALSA) as a detector, and using PDXL as analysis software. The measurement method can use the 2θ / θ method, and the analysis can be applied to the calculation method using the Scherrer formula based on the half-value width of the peak.

[0061] The copper chromium oxide spinel of the present invention may further contain molybdenum, sodium or potassium.

[0062] In the case of containing molybdenum, the molybdenum content contained in the copper chromium oxide spinel can be measured by X-ray fluorescence (XRF) analysis. The content (Mo1) obtained by XRF analysis of the copper chromium oxide spinel of the embodiment is preferably 0.03 mass % or more, more preferably 0.03 mass % to 5.0 mass %, and further preferably 0.1 mass % to 2.5 mass %.

[0063] In the XRF analysis, a fluorescent X-ray analysis device (for example, Primus IV manufactured by Rigaku Co., Ltd.) can be used.

[0064] The content (Mo1) calculated by MoO3 conversion refers to the value obtained by converting the molybdenum content obtained by XRF analysis of copper chromium oxide spinel according to the calibration curve converted by MoO3. In addition, the content (Mo1) is the content (Mo1) relative to 100% by mass of the copper chromium oxide spinel.

[0065] The molybdenum content contained in the surface layer of the copper chromium oxide spinel can be measured by X-ray photoelectron spectroscopy (XPS) surface analysis. The molybdenum content in the surface layer of the copper chromium oxide spinel of the embodiment is preferably 0.03 mass % or more, and preferably 0.03 mass % to 15.0 mass %, more preferably 0.5 mass % to 10.0 mass %, and further preferably 0.5 mass % to 7.0 mass %. By being within the range, the copper of the copper chromium oxide spinel exposed by laser irradiation is more activated, and plating is easy to combine, so it is preferred.

[0066] In the XPS analysis, a scanning X-ray photoelectron spectrometer (for example, QUANTERA SXM manufactured by Ulvac-phi) can be used.

[0067] The content (Mo2) mentioned above refers to the following value: by performing XPS surface analysis on copper chromium oxide spinel, obtaining the existence ratio (atom %) of each element, converting the molybdenum content into oxide, and thus calculating the MoO3 content relative to 100 mass % of the surface layer of the copper chromium oxide spinel.

[0068] It is preferred that the molybdenum is preferentially present in the surface layer of the copper chromium oxide spinel.

[0069] Here, the term "surface layer" in this specification means within 10 nm from the surface of the copper chromium oxide spinel of the embodiment. This distance corresponds to the detection depth of XPS used for measurement in the examples.

[0070] Here, “existing predominantly in the surface layer” means a state in which the mass of molybdenum or the molybdenum compound per unit volume of the surface layer is greater than the mass of molybdenum or the molybdenum compound per unit volume of the area other than the surface layer.

[0071] In copper chromium oxide spinel, molybdenum tends to be present in the surface layer of the copper chromium oxide spinel, which can be confirmed as follows: the molybdenum content (Mo2) calculated based on MoO3 relative to 100 mass % of the surface layer of the copper chromium oxide spinel obtained by performing XPS surface analysis on the copper chromium oxide spinel is greater than the molybdenum content (Mo1) calculated based on MoO3 relative to 100 mass % of the copper chromium oxide spinel obtained by performing XRF (fluorescent X-ray) analysis on the copper chromium oxide spinel.

[0072] In copper chromium oxide spinel, as an indicator of molybdenum being preferentially present in the surface layer of the copper chromium oxide spinel, the surface-preferred molybdenum content (Mo2 / Mo1) of the copper chromium oxide spinel of the embodiment, which is the content (Mo2) obtained by XPS surface analysis relative to the content (Mo1) obtained by XRF analysis, is preferably greater than 1.0, more preferably greater than 2.0, and is preferably less than 300, more preferably less than 50, and further preferably less than 30.

[0073] When molybdenum or a molybdenum compound is contained, copper chromium oxide spinel having a desired particle size distribution can be easily obtained, and properties derived from molybdenum can be obtained. In particular, by making molybdenum or a molybdenum compound be present preferentially in the surface layer of copper chromium oxide spinel, compared with the case where molybdenum or a molybdenum compound is uniformly present not only in the surface layer but also outside the surface layer (inner layer), excellent properties such as catalytic activity can be efficiently imparted.

[0074] In addition, when containing molybdenum, the copper content contained in the copper chromium oxide spinel is preferably 25.0 mass% or more, more preferably 30.0 mass% to 40.0 mass%, and further preferably 32.0 mass% to 35.0 mass%, based on the content (Cu1) determined by XRF analysis.

[0075] The so-called CuO-converted content (Cu1) refers to the value obtained by converting the copper content obtained by XRF analysis of copper chromium oxide spinel according to the calibration curve using CuO conversion. In addition, the content (Cu1) is the content (Cu1) relative to 100% by mass of the copper chromium oxide spinel.

[0076] The copper content contained in the surface layer of copper chromium oxide spinel can be measured by XPS surface analysis. The copper content in the surface layer of copper chromium oxide spinel is preferably 50.0 mass % or more, preferably 50.0 mass % to 80.0 mass %, and more preferably 60.0 mass % to 75.0 mass %, based on the content (Cu2) obtained by XPS surface analysis of the copper chromium oxide spinel. By being within the range, there is a large amount of copper in the copper chromium oxide spinel activated by laser irradiation, and plating is easy to combine, so it is preferred.

[0077] The content (Cu2) refers to the following value: by performing XPS surface analysis on copper chromium oxide spinel, obtaining the existence ratio (atom %) of each element, converting the copper content into oxides, and thus calculating the CuO content relative to 100 mass % of the surface layer of the copper chromium oxide spinel.

[0078] In the copper chromium oxide spinel, it is preferred that the copper is preferentially present in the surface layer of the copper chromium oxide spinel.

[0079] Here, “existing predominantly in the surface layer” refers to a state in which the mass of copper or the copper compound per unit volume of the surface layer is greater than the mass of copper or the copper compound per unit volume of the area outside the surface layer.

[0080] In copper chromium oxide spinel, copper is biased toward being present in the surface layer of the copper chromium oxide spinel, as shown in the examples described later, and this can be confirmed by the following method, that is, the content (Cu2) obtained by performing XPS surface analysis on the copper chromium oxide spinel is greater than the content (Cu1) obtained by performing XRF analysis on the copper chromium oxide spinel.

[0081] In copper chromium oxide spinel, as an indicator that copper is preferentially present in the surface layer of the copper chromium oxide spinel, the surface-biased copper content (Cu2 / Cu1) of the copper chromium oxide spinel of the embodiment (Cu2) obtained by XPS surface analysis relative to the content (Cu2) obtained by XRF analysis is preferably greater than 1, more preferably greater than 1.25, particularly preferably greater than 1.5, and preferably less than 3, more preferably less than 2.5.

[0082] By making copper or copper compounds tend to be present in the surface layer of copper chromium oxide spinel, compared with the case where copper or copper compounds are uniformly present not only in the surface layer but also outside the surface layer (inner layer), the copper of the activated copper chromium oxide spinel is exposed in large quantities on the surface by laser irradiation, resulting in an increase in the number of bonding points with the plating, thereby improving the adhesion of the plating and thus being preferred.

[0083] <Method for producing copper chromium oxide spinel>

[0084] The method for producing copper chromium oxide spinel includes calcining a copper compound and a chromium compound. More specifically, the method may include mixing the copper compound and the chromium compound to prepare a mixture and calcining the mixture, but is not particularly limited.

[0085] A preferred method for producing copper chromium oxide spinel includes: a step of mixing a copper compound and a chromium compound to prepare a mixture (mixing step); and a step of calcining the mixture (calcining step).

[0086] [Mixing process]

[0087] The mixing step is a step of mixing the copper compound and the chromium compound to prepare a mixture.

[0088] The mixing method is not particularly limited, and simple mixing of the copper compound powder and the chromium compound powder, mechanical mixing using a pulverizer or the like, mixing using a mortar or the like, and mixing in a dry state or a wet state may be used.

[0089] For example, as the mixing in a wet state, there is a method of adding a powder of a copper compound and a powder of a chromium compound to a liquid medium and mixing them using a stirring mill.

[0090] As the liquid medium, an organic solvent, oil, water or the like can be used, but water is preferred in view of ease of post-treatment.

[0091] The stirring mill is not particularly limited as long as it is a medium stirring mill using a medium medium (beads, balls, sand), and examples thereof include a bead mill, a ball mill, a sand mill, and a paint shaker. In terms of ease of operation, a paint shaker using balls as a medium is preferred.

[0092] From the viewpoint of mixing the raw materials, the stirring time may be 5 to 240 minutes, 30 to 180 minutes, or 60 to 180 minutes.

[0093] For example, as mixing in a dry state, there can be listed manual methods such as putting the powder of the copper compound and the powder of the chromium compound into a bag and shaking or kneading them, or a ball mill, tube mill, vibration mill, planetary mill, etc. using medium media (beads, balls, sand), etc. In terms of ease of operation, a planetary mill using balls as the medium is preferred.

[0094] (Copper compounds)

[0095] The type of the copper compound is not particularly limited. For example, the copper compound may be a monovalent or divalent compound, such as copper chloride, copper sulfate, copper sulfide, copper carbonate, copper oxide, etc., and copper carbonate and copper oxide are preferred from the perspective of easy availability.

[0096] The shape of the calcined copper chromium oxide spinel hardly reflects the shape of the raw copper compound, so as the copper compound, for example, spherical, amorphous, vertically and horizontally structured (wires, fibers, strips, tubes, etc.), sheets, etc. can also be suitably used.

[0097] (Chromium compounds)

[0098] The type of the chromium compound is not particularly limited. For example, examples of the chromium compound include chromium chloride, chromium sulfate, chromium sulfide, chromium carbonate, and chromium oxide. From the viewpoint of easy availability, chromium carbonate and chromium oxide are preferred.

[0099] The shape of the calcined copper oxide chromium spinel hardly reflects the shape of the raw material chromium compound, and therefore, for example, spherical, amorphous, vertically and horizontally structured bodies (wires, fibers, strips, tubes, etc.), sheets, etc. can be suitably used as the chromium compound.

[0100] In the method for producing copper chromium oxide spinel of the present invention, the molar ratio of chromium to copper (Cu / Cr) in the raw material, for example, the mixture, is based on 2, but excess products or raw materials can be easily removed by the refining process described in detail later, so the Cu / Cr can be in the range of 1.5 to 2.5.

[0101] The method for producing copper chromium oxide spinel may further use a molybdenum compound during calcination. The production method may include a step of mixing a copper compound, a chromium compound, and a molybdenum compound to form a mixture before the calcination step (mixing step), and may include a step of calcining the mixture (calcination step).

[0102] By calcining a copper compound and a chromium compound in the presence of a molybdenum compound, highly crystalline polyhedral particles can be obtained compared to the case where no molybdenum compound is used. Copper oxide chromium spinel with the desired particle size and particle size distribution can be obtained without going through the crushing and / or classification steps described later, which is preferred in terms of simplifying the manufacturing process.

[0103] (Molybdenum compounds)

[0104] Examples of the molybdenum compound include molybdenum oxide, molybdic acid, molybdenum sulfide, molybdenum silicide, silicomolybdic acid, magnesium molybdate, and molybdate compounds, and molybdenum oxide is preferred.

[0105] Examples of the molybdenum oxide include molybdenum dioxide (MoO 2 ) and molybdenum trioxide (MoO 3 ), and molybdenum trioxide is preferred.

[0106] The molybdate compound is only MoO4 2- 、Mo2O7 2- 、Mo3O 10 2- 、Mo4O 13 2- 、Mo5O 16 2- 、Mo6O 19 2- 、Mo7O 24 6- 、Mo8O 26 4- The salt compound of the molybdenum oxide anion is not limited. It can be an alkali metal salt of the molybdenum oxide anion, an alkaline earth metal salt, or an ammonium salt.

[0107] Examples of the molybdate compound include alkali metal salts of molybdenum oxyanions, such as lithium molybdate, potassium molybdate, or sodium molybdate.

[0108] The molybdate compound may be a hydrate.

[0109] The molybdenum compound is preferably at least one compound selected from the group consisting of molybdenum trioxide, lithium molybdate, potassium molybdate, and sodium molybdate, more preferably at least one compound selected from the group consisting of molybdenum trioxide, potassium molybdate, and sodium molybdate, particularly preferably molybdenum trioxide and sodium molybdate.

[0110] When a molybdate compound is used, a molybdate compound formed by calcining a mixture of molybdenum oxide and a metal chloride (e.g., a metal carbonate, a halide, a sulfate, etc.) in advance may be used. For example, in the case of sodium molybdate, sodium molybdate formed by calcining a mixture of molybdenum oxide and sodium carbonate may be used.

[0111] In the method for producing copper chromium oxide spinel, a molybdenum compound is used as a flux. In this specification, the production method using a molybdenum compound as a flux is sometimes referred to as a "flux method" below. In addition, through the calcination, the copper compound, the chromium compound, and the molybdenum compound react at a high temperature, and a portion of them forms copper molybdate and chromium molybdate. It is believed that the copper molybdate and chromium molybdate further decompose at a high temperature accompanied by the formation of copper chromium oxide spinel, at which time a portion of the molybdenum oxide is introduced into the copper chromium oxide spinel. It is believed that a portion of the molybdenum oxide evaporates and is removed outside the system, but in the case of using sodium molybdate or the like as the molybdenum compound, the alkali metal compound and the molybdenum oxide are easily combined to form molybdate again, which is hardly discharged from the system and remains in the system.

[0112] It is believed that in the flux method, when sodium molybdate is used, for example, copper molybdate and chromium molybdate decompose in the presence of liquid sodium molybdate to form copper chromite, which then crystallizes and grows, thereby easily obtaining copper chromium oxide spinel with low or no aggregation while suppressing the evaporation of the flux (sublimation of MoO3). It is assumed that the above effect can also be obtained in molybdenum compounds and the like.

[0113] In the method for producing copper chromium oxide spinel, the amounts of the copper compound, chromium compound, and molybdenum compound used are not particularly limited. In the raw material, for example, in the mixture, the molybdenum compound can be formulated in an amount of 1 to 1000 parts by mass, or in an amount of 5 to 100 parts by mass, relative to 100 parts by mass of the total amount of the copper compound and the chromium compound.

[0114] In the method for producing copper chromium oxide spinel, the molar ratio of molybdenum atoms in the molybdenum compound in the raw material, such as the mixture, to copper and chromium atoms in the copper compound and the chromium compound (molybdenum / (copper+chromium)) is preferably greater than 0.001, more preferably greater than 0.003, further preferably greater than 0.01, and particularly preferably greater than 0.02.

[0115] The upper limit of the molar ratio of molybdenum atoms in the molybdenum compound in the raw material, for example, to copper and chromium atoms in the copper compound and chromium compound in the chromium compound can be appropriately determined. However, from the viewpoint of reducing the amount of molybdenum compound used and improving manufacturing efficiency, for example, the value of the molar ratio (molybdenum / (copper+chromium)) may be less than 1, less than 0.5, less than 0.2, or less than 0.1.

[0116] As an example of the numerical range of the molar ratio (molybdenum / (copper+chromium)) in the raw material, for example, in the mixture, the value of molybdenum / (copper+chromium) may be 0.001 to 1, 0.003 to 0.5, 0.01 to 0.2, or 0.02 to 0.1.

[0117] By using various compounds within the above range, the obtained copper chromium oxide spinel can be made into a desired particle diameter and particle size distribution without going through the pulverization and / or classification steps described later.

[0118] (Other additives)

[0119] In the method for producing copper chromium oxide spinel, a sodium compound and / or a potassium compound may be further used.

[0120] In the production method, by using a sodium compound and / or a potassium compound in combination, the particle size of the copper chromium oxide spinel to be produced can be easily adjusted, and copper chromium oxide spinel with little or no aggregation can be easily produced.

[0121] Here, when a molybdenum compound is used as a flux, a compound containing molybdenum and sodium such as sodium molybdate may be used to replace at least a portion of the molybdenum compound and the sodium compound. Similarly, a compound containing molybdenum and potassium such as potassium molybdate may be used to replace at least a portion of the molybdenum compound and the potassium compound.

[0122] The compound containing molybdenum and sodium suitable as a flux can be produced, for example, by using molybdenum compounds and sodium compounds, which are cheaper and more easily available, as raw materials during calcination. Here, the case where a molybdenum compound and a sodium compound are used as fluxes and the case where a compound containing molybdenum and sodium is used as fluxes are combined and regarded as the case where a molybdenum compound and a sodium compound are used as fluxes, that is, in the presence of a molybdenum compound and a sodium compound.

[0123] The compound containing molybdenum and potassium suitable as a flux can be produced, for example, by using molybdenum compounds and potassium compounds, which are cheaper and more easily available, as raw materials during calcination. Here, the case where a molybdenum compound and a potassium compound are used as flux and the case where a compound containing molybdenum and potassium are used as flux are combined and regarded as the case where a molybdenum compound and a potassium compound are used as flux, that is, in the presence of a molybdenum compound and a potassium compound.

[0124] (Sodium compounds)

[0125] The sodium compound is not particularly limited, and examples thereof include sodium carbonate, sodium molybdate, sodium oxide, sodium sulfate, sodium hydroxide, sodium nitrate, sodium chloride, metallic sodium, etc. Among these, sodium carbonate, sodium molybdate, sodium oxide, and sodium sulfate are preferably used from the viewpoint of industrial availability and ease of handling.

[0126] Furthermore, the sodium compounds may be used alone or in combination of two or more.

[0127] In addition, similarly to the above, sodium molybdate contains molybdenum and thus can also function as the molybdenum compound.

[0128] (Potassium compounds)

[0129] The potassium compound is not particularly limited, and examples thereof include potassium chloride, potassium chlorite, potassium chlorate, potassium sulfate, potassium hydrogen sulfate, potassium sulfite, potassium hydrogen sulfite, potassium nitrate, potassium carbonate, potassium hydrogen carbonate, potassium acetate, potassium oxide, potassium bromide, potassium bromate, potassium hydroxide, potassium silicate, potassium phosphate, potassium hydrogen phosphate, potassium sulfide, potassium hydrogen sulfide, potassium molybdate, potassium tungstate, etc. In this case, the potassium compound contains isomers in the same manner as the molybdenum compound. Among these, potassium carbonate, potassium hydrogen carbonate, potassium oxide, potassium hydroxide, potassium chloride, potassium sulfate, and potassium molybdate are preferably used, and potassium carbonate, potassium hydrogen carbonate, potassium chloride, potassium sulfate, and potassium molybdate are more preferably used.

[0130] Furthermore, the potassium compounds may be used alone or in combination of two or more.

[0131] In addition, similarly to the above, potassium molybdate contains molybdenum and thus can also function as the above-mentioned molybdenum compound.

[0132] (Metal Compounds)

[0133] In the method for producing copper chromium oxide spinel, a metal compound may be used during calcination as necessary.

[0134] The metal compound is not particularly limited, but preferably contains at least one selected from the group consisting of Group II metal compounds and Group III metal compounds.

[0135] Examples of the Group II metal compound include calcium compounds, strontium compounds, and barium compounds.

[0136] Examples of the Group III metal compound include scandium compounds, yttrium compounds, lanthanum compounds, and cerium compounds.

[0137] In addition, the metal compound refers to an oxide, hydroxide, carbonate, or chloride of a metal element. For example, if it is a yttrium compound, yttrium oxide (Y2O3), yttrium hydroxide, and yttrium carbonate can be cited. Among these, the metal compound is preferably an oxide of a metal element. In addition, these metal compounds include isomers.

[0138] Among these, metal compounds of the third period elements, metal compounds of the fourth period elements, metal compounds of the fifth period elements, and metal compounds of the sixth period elements are preferred, metal compounds of the fourth period elements and metal compounds of the fifth period elements are more preferred, and metal compounds of the fifth period elements are further preferred. Specifically, calcium compounds, yttrium compounds, and lanthanum compounds are preferably used, calcium compounds and yttrium compounds are more preferably used, and yttrium compounds are particularly preferred.

[0139] The metal compound is preferably used in a ratio of, for example, 0 mass % to 1.2 mass % (for example, 0 mol % to 1 mol %) relative to the total amount of the chromium compound used in the mixing step.

[0140] [Calcination process]

[0141] The calcining step is a step of calcining the mixture. The copper chromium oxide spinel of the embodiment is obtained by calcining the mixture.

[0142] The states of the copper compound and the chromium compound during calcination are not particularly limited as long as they exist in the same space.

[0143] The conditions of the calcination temperature are not particularly limited and can be appropriately determined in consideration of the particle size, particle size distribution, shape, etc. of the target copper chromium oxide spinel. The calcination temperature may be above 800° C., above 900° C., or above 1200° C. If the calcination temperature becomes higher, the shape of the copper chromium oxide spinel is controlled, which is preferred.

[0144] From the viewpoint of production efficiency, the heating rate may be 20°C / h to 600°C / h, 40°C / h to 500°C / h, 100°C / h to 400°C / h, or 200°C / h to 400°C / h.

[0145] Regarding the calcination time, it is preferred that the heating time to the prescribed calcination temperature is within the range of 15 minutes to 10 hours. The holding time at the calcination temperature can be set to more than 5 minutes, preferably within the range of 5 minutes to 30 hours. In order to efficiently form copper oxide chromium spinel, it is further preferred that the calcination temperature holding time is more than 2 hours, and particularly preferably the calcination temperature holding time is 2 hours to 15 hours.

[0146] The calcination environment is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing environment such as air or oxygen, or an inert environment such as nitrogen, argon, or carbon dioxide is preferred. In consideration of cost, an air environment is more preferred.

[0147] The apparatus for calcining is not necessarily limited, and a so-called calcining furnace can be used, for example, a roller hearth kiln, a pusher kiln, a rotary kiln, a tunnel kiln, a shuttle kiln, etc.

[0148] When a molybdenum compound is used as a flux, similar to the conventional flux method, there are advantages that crystal growth can be performed at a temperature far lower than the melting point of the target compound, and the crystal shape and particle size distribution can be precisely controlled.

[0149] When a molybdenum compound is used, the states of the copper compound, the chromium compound, and the molybdenum compound during calcination are not particularly limited as long as the molybdenum compound exists in the same space where it can act on the copper compound and the chromium compound.

[0150] When a molybdenum compound is used, the calcination temperature is not particularly limited and can be appropriately determined in consideration of the particle size, particle size distribution, shape, etc. of the target copper chromium oxide spinel. The calcination temperature may be 800°C or higher, 800°C or higher, or 900°C or higher.

[0151] When a molybdenum compound is used, for example, even under the condition that the maximum calcination temperature for calcining the copper compound and the chromium compound is 1500° C. or less, copper chromium oxide spinel can be efficiently formed at low cost.

[0152] Even if the calcination temperature is much lower than 1500° C., copper chromium oxide spinel having a self-shaped structure can be formed regardless of the shape of the precursor. In addition, from the perspective of efficiently producing copper chromium oxide spinel, the calcination temperature may be 1500° C. or lower, or 1000° C. or lower.

[0153] When a molybdenum compound is used, the numerical range of the calcination temperature for calcining the copper compound and the chromium compound in the calcination step may be, for example, 700°C to 1500°C, 800°C to 1200°C, 900°C to 1000°C, or 950°C to 1000°C.

[0154] When a molybdenum compound is used, the heating rate may be 20 to 600°C / h, 40 to 500°C / h, 100 to 400°C / h, or 200 to 400°C / h from the viewpoint of production efficiency.

[0155] By being within the above range, particles having a narrow particle size distribution tend to be formed.

[0156] When using a molybdenum compound, the calcination time is preferably carried out in a range of 15 minutes to 10 hours to a predetermined calcination temperature. The holding time at the calcination temperature can be set to 5 minutes or more, preferably in a range of 5 minutes to 30 hours. In order to efficiently form copper oxide chromium spinel, the calcination temperature holding time is preferably 2 hours or more, and particularly preferably 2 hours to 15 hours.

[0157] The calcination environment is not particularly limited as long as the effects of the present invention can be obtained. For example, an oxygen-containing environment such as air or oxygen, or an inert environment such as nitrogen, argon, or carbon dioxide is preferred. In consideration of cost, an air environment is more preferred.

[0158] When a molybdenum compound is used, the apparatus for calcination is not necessarily limited, and a so-called calcination furnace can be used. The calcination furnace is preferably made of a material that does not react with the sublimated molybdenum oxide, and a calcination furnace with high airtightness is preferably used to more efficiently utilize the molybdenum oxide.

[0159] [Cooling process]

[0160] The method for producing copper chromium oxide spinel may include a cooling step. The cooling step is a step of cooling the copper chromium oxide spinel after crystal growth in the calcining step.

[0161] The cooling rate is not particularly limited, but is preferably 1°C / hour to 1000°C / hour, more preferably 5°C / hour to 500°C / hour, and further preferably 50°C / hour to 100°C / hour. If the cooling rate is 1°C / hour or more, the manufacturing time can be shortened, so it is preferred. On the other hand, if the cooling rate is 1000°C / hour or less, the calcination container is less likely to be broken due to thermal shock, and can be used for a long time, so it is preferred.

[0162] The cooling method is not particularly limited, and the product may be cooled naturally or by using a cooling device.

[0163] [Post-processing process]

[0164] When a molybdenum compound is used in the method for producing copper chromium oxide spinel, a post-treatment step of removing at least a portion of the molybdenum may be further included after the calcining step, if necessary.

[0165] Examples of the method include washing and high temperature treatment, which may be performed in combination.

[0166] Molybdenum may be attached to the surface of copper chromium oxide spinel. The molybdenum may be removed by washing with water, an aqueous ammonia solution, an aqueous sodium hydroxide solution, or the like.

[0167] At this time, the molybdenum content in the copper chromium oxide spinel can be controlled by appropriately changing the concentration, amount, cleaning location, cleaning time, etc. of the water, ammonia solution, and sodium hydroxide solution used.

[0168] In addition, as a method of high temperature treatment, there is a method of raising the temperature to a temperature above the sublimation point or boiling point of the molybdenum compound.

[0169] [Crushing process]

[0170] The calcined product obtained through the calcination step may be agglomerated and fail to satisfy the appropriate particle size range in the intended application. Therefore, the copper chromium oxide spinel may be pulverized as necessary to satisfy the appropriate particle size range.

[0171] The method for pulverizing the calcined product is not particularly limited, and a conventionally known pulverization method such as a ball mill, a jaw crusher, a jet mill, a disc mill, a Spectromill, a grinder, a mixer mill, etc. can be applied.

[0172] [Grading process]

[0173] In order to adjust the range of particle diameters, the calcined product containing copper chromium oxide spinel obtained by the calcination step may be appropriately subjected to classification. The so-called "classification" refers to an operation of grouping particles according to their sizes.

[0174] The classification may be performed by either a wet method or a dry method, but dry classification is preferred from the viewpoint of productivity.

[0175] In dry classification, in addition to classification using a sieve, there is also wind classification that performs classification based on the difference between centrifugal force and fluid resistance. From the viewpoint of classification accuracy, wind classification is preferred, and can be performed using classifiers such as an airflow classifier utilizing the Coanda effect, a cyclonic airflow classifier, a forced vortex centrifugal classifier, and a semi-free vortex centrifugal classifier.

[0176] The pulverization step or classification step may be performed at a desired stage. The average particle size of the copper chromium oxide spinel obtained can be adjusted, for example, by the presence or absence of the pulverization or classification or by selecting the conditions thereof.

[0177] The copper chromium oxide spinel of the embodiment or the copper chromium oxide spinel obtained by the manufacturing method of the embodiment has little or no aggregation, so it is easy to exert its original properties, its own handleability is better, and when it is dispersed in a dispersion medium for use, the dispersibility is better, which is preferred from this point of view.

[0178] In addition, when molybdenum is used in the method for producing copper chromium oxide spinel, copper chromium oxide spinel with little or no agglomeration can be easily produced, so it has the following excellent advantage: even if the above-mentioned crushing process or classification process is not carried out, copper chromium oxide spinel with target excellent properties can be produced with high productivity.

[0179] (use)

[0180] The copper chromium oxide spinel of the present invention has a precisely controlled particle size or particle size distribution and can therefore be suitably used in catalysts or resin compositions. Specifically, examples thereof include, but are not limited to, synthesis reaction catalysts, exhaust gas purification catalysts, heat-resistant pigments, and resin compositions for LDS.

[0181] <Resin composition>

[0182] The copper chromium oxide spinel of the present invention can be suitably used in resin compositions, and can be particularly suitably used as a resin composition for LDS. Specifically, as a method for obtaining a resin composition from the copper chromium oxide spinel of the present invention, it can be obtained in the following manner: using an extruder, a kneader, a roller, etc. as needed, the copper chromium oxide spinel, a thermoplastic resin, and an inorganic filler are fully melt-kneaded until they are uniform, and the kneaded product is cooled. In addition, regarding the shape of the obtained resin composition, when a thermoplastic resin is used, it can be any shape such as granules, and when a thermosetting resin is used, it can be crushed into an appropriate size and made into a flat plate shape by a tablet molding machine, etc.

[0183] The resin composition for LDS may further contain clay minerals, fillers, coupling agents, and other additives as optional components.

[0184] The content of copper chromium oxide spinel in the resin composition relative to 100 parts by mass of the resin composition is contained as a lower limit exceeding 0 parts by mass, preferably 1 part by mass or more, more preferably 5 parts by mass or more, and is preferably less than 30 parts by mass, more preferably less than 20 parts by mass as an upper limit. By being within the above range, the plating property of the obtained molded product can be made good.

[0185] As the thermoplastic resin, there is no particular limitation, and examples thereof include polyester resin, polyarylene sulfide resin, polyamide resin, polyimide resin, polyetherimide resin, polycarbonate resin, polyphenylene oxide resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, syndiotactic polystyrene resin, polyethylene resin, polypropylene resin, polytetrafluoroethylene resin, polyvinylidene fluoride resin, polystyrene resin, acrylonitrile-butadiene-styrene (ABS) resin, phenolic resin, carbamate resin, liquid crystal polymer, etc. These resins can be used alone or in combination of two or more. Among these, preferably polyarylene sulfide resin, polyamide resin, polyetherimide resin, polycarbonate resin, polyphenylene oxide resin, polysulfone resin, polyethersulfone resin, polyetheretherketone resin, polyetherketone resin, polyarylene resin, syndiotactic polystyrene resin, in terms of the viewpoint of maintaining the close contact force of plating, particularly preferably polyarylene sulfide resin and polyamide resin with high laser sensitivity.

[0186] As the thermosetting resin, there is no particular limitation, and examples thereof include epoxy resin, phenolic resin, oxetane resin, (meth)acrylate resin, unsaturated polyester resin, diallyl phthalate resin, maleimide resin, etc. These resins can be used alone or in combination of two or more. Among these, epoxy resin is particularly preferred from the viewpoint of improving curability, storage property, heat resistance, moisture resistance, and chemical resistance.

[0187] Relative to the total mass of the resin composition, the thermoplastic resin or the thermosetting resin is preferably in a range of 5% by mass or more, more preferably 10% by mass or more, preferably 40% by mass or less, more preferably 20% by mass or less. If the thermoplastic resin or the thermosetting resin is in a range of 5% by mass or more relative to the total mass of the resin composition, the plating precipitation speed of the obtained molded product can be increased, and therefore it is preferred. In addition, from the perspective of the plating adhesion of the obtained molded product, the filling property or the molding stability, it is preferably 40% by mass or less.

[0188] As the inorganic filler, there can be cited: fused silica, crystalline silica, white silica, aluminum oxide, silicon nitride, aluminum nitride, aluminum hydroxide, boron nitride, titanium oxide, glass fiber, aluminum oxide fiber, zinc oxide, talc, calcium carbide, etc. These inorganic fillers can be used alone, or two or more can be used in combination. From the viewpoint of improving the dispersibility of the resin composition, fused silica and crystalline silica are more preferably used, and from the viewpoint of improving the mechanical strength of the molded product, glass fiber is more preferably used.

[0189] The resin composition may be formulated with a clay mineral as an arbitrary component. The clay mineral exerts a synergistic effect with the copper chromium oxide spinel of the present invention, and has the function of improving the plating property of the obtained molded product and the bonding strength of the plating layer. In terms of obtaining a practical plating precipitation rate for the obtained molded product, the clay mineral is preferably uniformly contained in the resin composition like the copper chromium oxide spinel.

[0190] As the clay mineral, a layered clay mineral having cleavage properties can be used. The clay mineral is not particularly limited, and examples thereof include carbonate minerals and silicate minerals.

[0191] As the filler, there is no particular limitation, and examples thereof include: fibrous fillers such as carbon fiber, silane glass fiber, ceramic fiber, aramid fiber, metal fiber, potassium titanate fiber, silicon carbide fiber, calcium silicate (wollastonite); non-fibrous fillers such as glass beads, glass flakes, barium sulfate, clay, pyrophyllite, bentonite, sericite, magnesium aluminum sepiolite (Attapulgite), ferrite, calcium silicate, calcium carbonate, magnesium carbonate, glass beads, zeolite, and calcium sulfate. These fillers can be used alone or in combination of two or more. These fillers have the function of further imparting mechanical strength to the molded product.

[0192] Examples of the coupling agent include silane coupling agents: epoxy group-containing alkoxysilane compounds such as γ-glycidyloxypropyltrimethoxysilane, γ-glycidyloxypropyltriethoxysilane, and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane; γ-isocyanatopropyltrimethoxysilane, γ-isocyanatopropyltriethoxysilane, γ-isocyanatopropylmethyldimethoxysilane, γ-isocyanatopropylmethyldiethoxysilane, γ-isocyanatopropyltrimethoxysilane, and γ-isocyanatopropyltriethoxysilane. Alkoxysilane compounds containing isocyanate groups such as ethyl dimethoxysilane, γ-isocyanatopropyl ethyl diethoxysilane, and γ-isocyanatopropyl trichlorosilane; alkoxysilane compounds containing amino groups such as γ-(2-aminoethyl)aminopropyl methyl dimethoxysilane, γ-(2-aminoethyl)aminopropyl trimethoxysilane, and γ-aminopropyl trimethoxysilane; alkoxysilane compounds containing hydroxy groups such as γ-hydroxypropyl trimethoxysilane and γ-hydroxypropyl triethoxysilane. These silane coupling agents may be used alone or in combination of two or more. These coupling agents have the function of imparting mechanical strength to molded products in addition to imparting adhesion to different materials.

[0193] Examples of the other additives include hardeners, hardening accelerators, release agents, flame retardants, light stabilizers, heat stabilizers, alkalis, elastomers, titanium oxide, antioxidants, hydrolysis resistance improvers, matting agents, ultraviolet absorbers, nucleating agents, plasticizers, dispersants, antistatic agents, anti-coloring agents, anti-gelling agents, colorants, and the like.

[0194] <Resin molded products>

[0195] The method for obtaining a resin molded product from the resin composition of the present invention is not particularly limited, and a known method can be appropriately adopted, for example, injection molding, injection compression molding, mold molding such as transfer molding, extrusion molding, sheet molding, thermoforming, rotational molding, lamination molding, press molding, blow molding, melt molding, etc.

[0196] The obtained molded product is roughened by direct laser molding on the surface or inside, and then plated. The plating can be precipitated only in the roughened area, so it is suitable for use in circuits of built-in antennas or touch sensors and chip packages.

[0197] Laser is a method for roughening the surface layer. The wavelength of the laser can be appropriately selected from the range of 150 nm to 12,000 nm, and is preferably 185 nm, 248 nm, 254 nm, 308 nm, 355 nm, 532 nm, 1,064 nm or 10,600 nm.

[0198] As a plating treatment, it can be any of electrolytic plating or electroless plating. Through the laser irradiation, the surface layer of the molded product is roughened, and a part of the activated copper oxide chromium spinel in the resin composition is exposed. Thus, during the plating treatment, the plating is only precipitated in the roughened area, so that a circuit can be formed. As a plating solution, there is no particular limitation, and a known plating solution can be used appropriately, and a plating solution containing necessary metal components such as Cu, Ni, and Ag can be used.

[0199] The method for confirming whether the copper chromium oxide spinel of the present invention is suitable for LDS applications is not particularly limited, and evaluation can be performed, for example, by observing aggregated particles in the dispersion, observing the distribution of metal elements in the dispersion, or measuring the surface roughness of the cured resin.

[0200] As a method for directly observing the aggregated particles of the dispersion, the following method can be cited: after preparing a dispersion containing the copper chromium oxide spinel of the present invention, a resin, and a solvent, the dispersion is visually observed to confirm the presence or absence of aggregates of the copper chromium oxide spinel. When no aggregates are observed, it can be evaluated as "good dispersibility (hereinafter, ○)", and when aggregates are observed, it can be evaluated as "poor dispersibility (hereinafter, ×)".

[0201] There is no particular limitation on the resin, and for example, the thermosetting resin and thermoplastic resin can be used. In addition, a dispersant can also be used instead of the resin. As the dispersant, a known dispersant can be used appropriately, and for example, polymer dispersants such as carbamate dispersants, acrylic acid dispersants, polyethyleneimine dispersants, polyallylamine dispersants, polyoxyethylene alkyl ether dispersants, polyoxyethylene diester dispersants, polyether phosphoric acid dispersants, polyester phosphoric acid dispersants, sorbitan aliphatic ester dispersants, and aliphatic modified polyester dispersants can be listed. In addition, the resin and the dispersant can be used together, or the resin or the dispersant can be not used, and only the solvent and copper oxide chromium spinel can be used to prepare the dispersion.

[0202] The solvent may be an organic solvent or water. The organic solvent is not particularly limited, and examples thereof include alcohols such as methanol, ethanol, propanol, isopropanol, butanol, hexanol, heptanol, octanol, decanol, cyclohexanol, terpineol, 1-methoxy-2-propanol, glycols such as ethylene glycol and propylene glycol, ketones such as acetone, ethyl ketone, methyl ethyl ketone, and diethyl ketone, esters such as ethyl acetate, butyl acetate, and benzyl acetate, ether alcohols such as methoxyethanol and ethoxyethanol, and ethers such as dioxane and tetrahydrofuran. Acid amides such as N,N-dimethylformamide, aromatic hydrocarbons such as benzene, toluene, xylene, trimethylbenzene, dodecylbenzene, etc., organic chlorine compounds such as chloroform, chlorobenzene, o-dichlorobenzene, hexane, heptane, octane, nonane, decane, undecane, dodecane, tridecane, tetradecane, pentadecane, hexadecane, octadecane, nonadecane, eicosane, trimethylpentane, etc. long chain alkanes, cyclohexane, cycloheptane, cyclooctane, decahydronaphthalene, etc. cyclic alkanes, etc.

[0203] As the dispersion method, a method of mixing using a disperser such as a paint conditioner, a bead mill, a ball mill, a blender mill, a three-roll mill, or an ultrasonic homogenizer can be used.

[0204] The dispersion state can be confirmed by preparing a cured resin and calculating the roughness of the cured surface. The presence of irregularities on the cured surface means that agglomerates (secondary particles) or coarse particles (primary particles) are present due to insufficient control of particle diameter or particle size distribution.

[0205] The cured resin can be produced according to the method described in the resin composition and the resin molded product.

[0206] The surface roughness can be measured in accordance with JIS B0601 (1994).

[0207] Alternatively, the evaluation can be performed by dropping or applying a color developing composition containing copper chromium oxide spinel, a water-soluble binder, a dispersant, and a defoaming agent onto a substrate and observing the surface state of a coating film obtained by curing the composition.

[0208] Examples of the water-soluble binder include styrene acrylic resin emulsions, (meth)acrylate resin emulsions, and polybutadiene resin emulsions.

[0209] Examples of the dispersant include phosphate-based dispersants, and among them, sodium hexane metaphosphate and sodium pyrophosphate are preferred.

[0210] As the defoaming agent, preferably, a silicone defoaming agent is used, and any of an emulsified dispersion type and a solubilized type can be used.

[0211] As the evaluation method of dispersibility, it can be any one of the evaluation by visual observation or metal element analysis. In the former case, if longitudinal stripes (color unevenness) are generated in the coating film, it can be judged as poor dispersibility. In the latter case, the deviation of the element is evaluated based on the profile representing the peak intensity of Cu and Cr. If the bias exists in a part, it can be judged as poor dispersibility.

[0212] Example

[0213] Next, the present invention will be specifically described by way of examples and comparative examples. Unless otherwise specified, "parts" and "%" are by mass. In addition, copper chromium oxide spinel was synthesized under the following conditions, and was measured or calculated under the following conditions for evaluation.

[0214] <Synthesis of copper chromium oxide spinel>

[0215] (Example 1)

[0216] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 1.16 parts of molybdenum trioxide (manufactured by Japan Inorganic Chemical Industry), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 950°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.2% by mass, Mo2 was 5.4% by mass, Cu1 was 33.7% by mass, and Cu2 was 62.7% by mass.

[0217] (Example 2)

[0218] Copper chromium oxide spinel was obtained in the same manner as in Example 1 except that the amount of molybdenum trioxide used was changed to 2.32 parts. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.3 mass %, Mo2 was 3.9 mass %, Cu1 was 33.4 mass %, and Cu2 was 71.7 mass %.

[0219] (Example 3)

[0220] A mixture of 38.6 parts of sodium molybdate dihydrate (a reagent manufactured by Kanto Chemical) and 14.4 parts of molybdenum trioxide (manufactured by Nippon Inorganic Chemical Industry) was placed in a crucible and calcined at 700° C. for 5 hours in a ceramic electric furnace to obtain 49.0 parts of Na2Mo2O7.

[0221] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 2.32 parts of the above-mentioned Na2Mo2O7, 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 950°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.1% by mass, Mo2 was 0.8% by mass, Cu1 was 33.3% by mass, and Cu2 was 64.4% by mass.

[0222] (Example 4)

[0223] 7.95 parts of copper (II) oxide (reagent manufactured by Kanto Chemical Co., Ltd., CuO), 15.20 parts of chromium (III) oxide (reagent manufactured by Kanto Chemical Co., Ltd., Cr2O3), 1.16 parts of molybdenum trioxide (manufactured by Japan Inorganic Chemical Industry), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 900°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were subjected to XRF and XPS analysis, and the results showed that Mo1 was 0.1% by mass, Mo2 was 0.3% by mass, Cu1 was 32.9% by mass, and Cu2 was 55.9% by mass.

[0224] (Example 5)

[0225] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 2.32 parts of molybdenum trioxide (manufactured by Japan Inorganic Chemical Industry), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 950°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.2% by mass, Mo2 was 2.7% by mass, Cu1 was 33.2% by mass, and Cu2 was 61.6% by mass.

[0226] (Example 6)

[0227] A mixture of 38.6 parts of sodium molybdate dihydrate (a reagent manufactured by Kanto Chemical) and 14.4 parts of molybdenum trioxide (manufactured by Nippon Inorganic Chemical Industry) was placed in a crucible and calcined at 700° C. for 5 hours in a ceramic electric furnace to obtain 49.0 parts of Na2Mo2O7.

[0228] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 2.32 parts of the above-mentioned Na2Mo2O7, 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 900°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.1% by mass, Mo2 was 0.9% by mass, Cu1 was 33.4% by mass, and Cu2 was 51.2% by mass.

[0229] (Comparative Example 1)

[0230] 7.95 parts of copper (II) oxide (reagent, CuO manufactured by Kanto Chemical Co., Ltd.), 15.20 parts of chromium (III) oxide (reagent, Cr2O3 manufactured by Kanto Chemical Co., Ltd.), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 900°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a dark green powder. Next, the dark green powder was dispersed in 300 mL of 0.25% ammonia water, and the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, passed through a 100 μm sieve, filtered to remove the ammonia water, and washed with water and dried to obtain a dark green powder.

[0231] (Comparative Example 2)

[0232] 4.78 parts of copper (II) oxide (reagent manufactured by Kanto Chemical Co., Ltd., CuO), 15.00 parts of chromium (III) oxide (reagent manufactured by Kanto Chemical Co., Ltd., Cr2O3), 0.02 parts of molybdenum trioxide (manufactured by Japan Inorganic Chemical Industry), 0.20 parts of zinc oxide (reagent manufactured by Kanto Chemical Co., Ltd., ZnO), 30 parts of ion exchange water, and 120 parts of 5mmφ zirconium oxide beads were placed in a 100ml polypropylene bottle, and mixed and crushed for 120 minutes using a paint shaker to obtain a mixture. The obtained mixture was transferred to a metal ball bar, dried in an oven at 120°C, and the dried product was crushed using a mixer (manufactured by Osaka Chemical). The crushed raw materials were placed in a crucible and calcined at 900°C for 10 hours using a ceramic electric furnace. In addition, the temperature was raised at 5°C / minute. After cooling, the crucible was taken out to obtain a black powder. Then, the black powder was dispersed in 300 mL of 0.25% ammonia water, the dispersed solution was stirred at room temperature (25°C to 30°C) for 2 hours, and then passed through a 100 μm sieve, the ammonia water was removed by filtration, and the mixture was washed with water and dried to obtain copper oxide chromium spinel. In addition, the particles were analyzed by XRF and XPS, and the results showed that Mo1 was 0.1% by mass and Mo2 was 10.0% by mass.

[0233] [Particle size distribution measurement]

[0234] The particle size distribution of the sample powder was measured by dry method using a laser diffraction dry particle size distribution meter (HELOS (H3355) & RODOS manufactured by Japan Laser Co., Ltd.) under the conditions of dispersion pressure of 3 bar and tensile pressure of 90 mbar. The particle diameter at the point where the distribution curve of volume cumulative % intersects with the horizontal axis of 50% was calculated as D50. In addition, D10 and D90 were also calculated using the same method.

[0235] [SPAN value]

[0236] The spread of the particle size distribution is calculated using the following conversion formula.

[0237] SPAN=(D90-D10) / D50

[0238] [Appearance evaluation of color-developed objects]

[0239] <Preparation of color development composition>

[0240] Using a defoaming stirring taro manufactured by Thinky, 2.0 parts of the sample powder, 10 parts of a styrene acrylic resin emulsion (HIROS X, X-436, manufactured by Starlight PMC Co., Ltd., an aqueous dispersion containing 40% by mass of the resin), 0.6 parts of an aqueous solution of sodium hexane metaphosphate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd., a 5% by mass aqueous solution), and 0.5 parts of a VOC-free silicone defoamer (BYK-028, manufactured by BYK-Chemie Japan Co., Ltd., a 5% by mass aqueous solution) were mixed to obtain an ink composition.

[0241] The obtained ink composition was developed on inkjet paper using a bar coater #20, Φ10 mm (manufactured by ASONE Co., Ltd.), and then dried for 1 hour (at room temperature, in the air) to obtain a developed product.

[0242] <Appearance evaluation of color-developed objects>

[0243] The obtained color-developed product was visually evaluated according to the following items.

[0244] [Evaluation criteria for ink color development]

[0245] A (excellent): The color development is a uniform coating film without color unevenness, and there are no streaks caused by poor dispersion.

[0246] B (good): The color development is a uniform coating film without color unevenness, but there are some streaks due to poor dispersion.

[0247] C (Not acceptable): Streaks or uneven color are visible on the color display.

[0248] [Metal element analysis and evaluation]

[0249] <Sample production>

[0250] The obtained color-developed product was fixed on an aluminum plate, and gold was coated on the coating surface of the color-developed product using a magnetron sputtering device (manufactured by Vacuum Devices Co., Ltd.) to prepare a measurement sample.

[0251] <Sample measurement method>

[0252] For the measurement sample, a desktop SEM (JCM-7000, manufactured by JEOL) was used to scan the surface on a straight line of about 1 mm at an acceleration voltage of 15 kV, and the intensity of the energy region equivalent to the characteristic X-rays of Cr-Kα and Cu-Kα was measured.

[0253] <Metal element analysis and evaluation>

[0254] The profile showing the peak intensity of Cr and Cu at each point on the surface of the obtained sample was evaluated according to the following items.

[0255] [Evaluation criteria for outline]

[0256] A (excellent): The peaks of Cr and Cu are not biased, and the deviation of the peak intensity is small.

[0257] B (good): The peaks of Cr and Cu partially exist in a biased manner, but the variation in peak intensity is small.

[0258] C (unacceptable): There is a peak deviation of Cr and Cu, and the peak intensity has a large deviation.

[0259] [Table 1]

[0260]

[0261] *Total mass parts of MoO3 or Na2Mo2O7 relative to 100 mass parts of CuO and Cr2O3

[0262] [Table 2]

[0263]

[0264] According to Patent Document 3, it is estimated that the SPAN value of commercially available copper chromium oxide spinel (Balck 1G, manufactured by Sherpherd Color Company) exceeds 2, similarly to Comparative Examples 1 and 2, compared to the described particle diameter.

[0265] Explanation of symbols

[0266] 100: Inkjet paper

[0267] 110: Display of color objects

[0268] 120: Scanning direction of SEM

Claims

1. A copper chromium oxide spinel, wherein in a volume-converted particle size distribution obtained by a laser diffraction scattering method, when the particle sizes with cumulative frequencies of 10%, 50%, and 90% from the small particle size side are set as D10, D50, and D90, respectively, an expansion span of the particle size distribution = (D90-D10) / D50 is less than 2.

2. The copper chromium oxide spinel according to claim 1, wherein D50 is 5.0 μm or less.

3. The copper chromium oxide spinel according to claim 1 or 2, wherein D90 is 10.0 μm or less. The copper chromium oxide spinel according to claim 1 or 2, wherein the copper chromium oxide spinel is in the shape of an octahedron.

5. The copper chromium oxide spinel according to claim 1, further comprising molybdenum.

6. A resin composition comprising: the copper chromium oxide spinel according to claim 1 or 2; Thermoplastic resin or thermosetting resin; and Inorganic filler.

7. A resin molded product obtained by molding the resin composition according to claim 6.

Citation Information

Cited By

  • Composite oxide particles, method for producing the same, resin composition, and molded body

    WO2026188424A1

  • Composite oxide, method for producing the same, resin composition, and molded body

    WO2026188425A1